Liraglutide and sitagliptin counter beta- to alpha-cell transdifferentiation in diabetes. Issue 1 (April 2020) - Tanday, Neil; Flatt, Peter R; Irwin, Nigel; Moffett, R Charlotte
Abstract : Transdifferentiation of beta- to alpha-cells has been implicated in the pathogenesis of diabetes. To investigate the impact of contrasting aetiologies of beta-cell stress, as well as clinically approved incretin therapies on this process, lineage tracing of beta-cells in transgenic Ins1 Cre/+ / Rosa26-eYFP mice was investigated. Diabetes-like syndromes were induced by streptozotocin (STZ), high fat feeding (HFF) or hydrocortisone (HC), and effects of treatment with liraglutide or sitagliptin were investigated. Mice developed the characteristic metabolic features associated with beta-cell destruction or development of insulin resistance. Liraglutide was effective in preventing weight gain in HFF mice, with both treatments decreasing energy intake in STZ and HC mice. Treatment intervention also significantly reduced blood glucose levels in STZ and HC mice, as well as increasing either plasma or pancreatic insulin while decreasing circulating or pancreatic glucagon in all models. The recognised changes in pancreatic morphology induced by STZ, HFF or HC were partially, or fully, reversed by liraglutide and sitagliptin, and related to advantageous effects on alpha- and beta-cell growth and survival. More interestingly, induction of diabetes-like phenotype, regardless of pathogenesis, led to increased numbers of beta-cells losing their identity, as well as decreased expression of Pdx1 within beta-cells. Both treatment interventions, and especially liraglutide, countered detrimental islet cell transitioning effects in STZ and HFF mice. Only liraglutide imparted benefits on beta- to alpha-cell transdifferentiation in HC mice. These data demonstrate that beta- to alpha-cell transdifferentiation is a common consequence of beta-cell destruction or insulin resistance and that clinically approved incretin-based drugs effectively limit this.